Our experience of posterior polar cataract phacoemulsification - I. E. Ioshin; A. I. Tolchinskaya; A. A. Ozderbayeva; A. M. Baghirov (Российский офтальмологический журнал, 2020)
Purpose: to analyze posterior polar cataract (PPC) phacoemulsification results with regard to surgery technique.Materials and methods. 14 PPC patients (26 eyes) were examined; 8 of them under 50 years and 6, over 50. Before surgery, visual acuity was 0.3–0.6. The operations were performed by one and the same surgeon on an Infiniti Vision System phacoemulsifier (Alcon). In all cases, posterior chamber IOLs were implanted (in 24 cases, complete intracapsular fixation was achieved, in 2 cases, mixed fixation). The follow-up was 1 to 10 years. The main features of the proposed surgery technique: 1) to ensure a stable position of the anterior/posterior chamber, the introduction of solutions and  capsulorhexis are carried out through paracentesis before the main incision is made, 2) complete rejection of hydrodissection, hydrodelineation at the stage of preparation for the emulsification  of the core itself, as well as rejection of additional  hydrodissection of residual epinucleus before its aspiration, 3) the choice of constant torsion ultrasound mode to reduce the oscillatory movements of nuclear fragments, 4) reduction of hydrodynamic parameters (irrigation bottle height no more than 70 mm, aspiration no more than 30 cc/min, vacuum no more than 250 mmHg on the Infiniti  Vision System), 5) technique of sequential segmental stepwise fracture of the nucleus during emulsification  with minimal  rotation of fragments while reducing the ultrasonic power (up to 30%),  6) selection of a separate bimanual  irrigation / aspiration technique for a more predictable anterior chamber depth, in particular when extracting tips that can be carried out separately, 7) rejection of polishing the posterior capsule for the prevention of mechanical  contact and damage to the posterior capsule.Results. The postoperative period was uneventful. Best corrected visual acuity improved in all patients: to 0.4–0.5 (4), 0.6–0.8 (16), 0.9–1.0 (6). In the late postoperative period, 4 patients required a laser dissection of secondary opacities in the posterior lens capsule.Conclusion. The obtained functional results demonstrate the possibility of successful phacoemulsification with the minimum incidence of complications in patients with PPC. In the reported practice, the known surgical techniques aimed at reducing pressure fluctuations in the capsule bag as well as in the anterior chamber as a whole, were used.